Global Research on Emerging Mobile Learning for Senior High School Students: A Bibliometric Approach - Lili Safitri Diati; Fadhilah Fadhilah; Muhammad Giatman; Dedy Irfan (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to explore the global trends and research contributions related to mobile learning for high school students through a bibliometric approach. The PRISMA method and bibliometric tools (R Studio and biblioshiny) were employed to analyze 70 documents from Scopus and Web of Science databases. Results indicate significant growth in publications, with an annual growth rate of 12.93% from 2008 to 2024, highlighting increasing interest in mobile learning. Indonesia, Taiwan, and China were the most productive countries, with journals such as Computers and Education (IF: 8.5; Q1) being the most influential source. Keyword co-occurrence analysis revealed key themes, including learning personalization, mobile learning effectiveness, and critical thinking skill development. The results show that mobile learning contributes significantly to improving students' motivation and learning outcomes without adding pressure, especially through the integration of mobile technology with e-learning approaches. This study provides strategic insights for educators, policymakers, and researchers to optimize mobile learning implementation in high school education, while identifying future research opportunities.